2017
DOI: 10.1112/plms.12072
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of rational inner functions: geometry of singularities and integrability at the boundary

Abstract: Abstract. We analyze the singularities of rational inner functions on the unit bidisk and study both when these functions belong to Dirichlet-type spaces and when their partial derivatives belong to Hardy spaces. We characterize derivative H p membership purely in terms of contact order, a measure of the rate at which the zero set of a rational inner function approaches the distinguished boundary of the bidisk. We also show that derivatives of rational inner functions with singularities fail to be in H p for p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(83 citation statements)
references
References 44 publications
(102 reference statements)
2
81
0
Order By: Relevance
“…A geometric argument then gives the original claim. For a more detailed understanding of such varieties, which has been rapidly developed in recent years, see [1,3,2,7,5].…”
Section: 2mentioning
confidence: 99%
“…A geometric argument then gives the original claim. For a more detailed understanding of such varieties, which has been rapidly developed in recent years, see [1,3,2,7,5].…”
Section: 2mentioning
confidence: 99%
“…Furthermore, in [4] it is also shown that in higher dimensions it is no longer true that all partial derivatives must have the same H p integrability. Despite these limitations, in this article we prove certain results regarding regularity of the mixed partial derivative of RIFs in arbitrary dimension by proving inclusion for RIFs in certain Dirichlet type spaces; a problem more difficult than that addressed in [3] in the sense that we are dealing with both higher dimensions and higher order derivatives. Recall that D α 1 ,...,αn (D n ) is the space of holomorphic functions f (z 1 , .…”
Section: Introductionmentioning
confidence: 98%
“…In [8], Knese gives an algebraic classification of the ideal of polynomials p such that q/p lies in L 2 (T 2 ) for a fixed polynomial q, and furthermore proves that rational inner functions have non-tangential limits everywhere on the n−torus. In [3] and [5], a thorough analysis of the unimodular level sets and singular sets of RIFs gives a fairly complete understanding of the L p integrability on T 2 of the partial derivatives of RIFs in 2 variables. For instance it is shown that ∂ z 1 φ and ∂ z 2 φ have the same integrability properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have been studied extensively in the two and several variable settings. See, e.g., [2,3,4,21,7,25].…”
Section: Introductionmentioning
confidence: 99%